2008
DOI: 10.1603/0022-2585(2008)45[643:aoamsi]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Alternative Mating Strategies in <I>Anopheles gambiae</I>: Does Mating Occur Indoors?

Abstract: Mating in Anopheles gambiae has been observed only in outdoor swarms. Here we evaluate if mating also occurs indoors. Mark release recapture of virgin males and females in natural houses showed that mating occurred over a single day even when mosquitoes can leave the house through exit traps and without adaptation to laboratory conditions. In these experiments, insemination rate in the M molecular form of An. gambiae (and An. arabiensis) was higher than that of the S form (15% vs. 6%). Under these conditions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
43
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 34 publications
2
43
0
Order By: Relevance
“…Analysis of these swarms revealed a very low percentage of hybrids and few inter-specific copulae within them, which indicates the existence of assortative mating, most probably caused by pre-mating isolation mechanisms (Dabiré et al, 2013). However, Dao et al (2008) showed that when both species congregate inside huts, cross-species mating is as frequent as within-species mating, indicating that assortative mating breaks down when mating occurs indoors. This is consistent with reports observing the absence of assortative mating in lab-reared Anopheles colonies (Benedict et al, 2009;Paton et al, 2013), which, overall, suggests that chemical cues such as pheromones and cuticular hydrocarbons (Dao et al, 2008) and flight tones (Dao et al, 2008;Tripet et al, 2004) do not play a major role in species recognition.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of these swarms revealed a very low percentage of hybrids and few inter-specific copulae within them, which indicates the existence of assortative mating, most probably caused by pre-mating isolation mechanisms (Dabiré et al, 2013). However, Dao et al (2008) showed that when both species congregate inside huts, cross-species mating is as frequent as within-species mating, indicating that assortative mating breaks down when mating occurs indoors. This is consistent with reports observing the absence of assortative mating in lab-reared Anopheles colonies (Benedict et al, 2009;Paton et al, 2013), which, overall, suggests that chemical cues such as pheromones and cuticular hydrocarbons (Dao et al, 2008) and flight tones (Dao et al, 2008;Tripet et al, 2004) do not play a major role in species recognition.…”
Section: Discussionmentioning
confidence: 99%
“…A central challenge to extend understanding of phenotypic variation is the measurement of fitness (or its key components), under natural conditions. As demonstrated by larval transplantation studies with and without predators (Diabate et al 2005 vs. 2008) and by the absence of mating specificity indoors (Dao et al, 2008) as opposed to outdoors (Tripet 2001, Diabate et al 2006 and unpublished), natural environment is often distorted even by semi-field conditions, resulting in misleading results. Screened ‘greenhouses’ set in natural conditions e.g., (Knols et al, 2002) are undoubtedly valuable but cannot replace natural studies.…”
Section: Discussionmentioning
confidence: 99%
“…Additional evidence against olfactory cues involvement in mate recognitions was obtained from studies on indoor mating in Mali. Mark release recapture of virgin males and females in natural houses showed that mating occurred over a single day even when mosquitoes can leave the house through exit traps and without adaptation to laboratory conditions (Dao et al, 2008). Importantly, cross mating between the molecular forms occurred indoors as much as mating between members of the same form (Dao et al, 2008), indicating that chemical cues such as pheromones and cuticular hydrocarbons do not play a major role in form recognition, unless such signals are only released or perceived during swarming.…”
Section: Phenotypic Divergence Between the Molecular Formsmentioning
confidence: 99%
“…Mating of An. gambiae occurs primarily in swarms (Charlwood and Jones 1980, Diabate et al 2009), but the M form also mates indoors and exhibits behavior more similar to that observed in cages (Dao et al 2008). Females under field conditions can avoid repeated attempts of mating by males by flying away from swarms and departing houses after sunset.…”
Section: Discussionmentioning
confidence: 99%
“…As in many other mosquitoes, mating in Anopheles gambiae Giles occurs primarily in swarms (Charlwood and Jones 1980, Marchand 1984, Charlwood et al 2002b, Yuval 2006, Diabate et al 2009, Howell and Knols 2009), but also indoors (Dao et al 2008). After sunset, males form swarms that typically consist of 20–300 males flying in a cloud of ≈1 m diameter (Manoukis et al 2009) for 20–30 min.…”
mentioning
confidence: 99%